2010
DOI: 10.1007/s11482-010-9108-4
|View full text |Cite
|
Sign up to set email alerts
|

Migration Flows and Quality of Life in a Metropolitan Area: the Case of Barcelona-Spain

Abstract: The phenomenon of human migration is certainly not new and it has been studied from a variety of perspectives. Yet, the attention on human migration and its determinant has not been fading over time as confirmed by recent contributions (see for instance Cushing andPoot 2004 andRebhun andRaveh 2006). In this paper we combine the recent theoretical contributions by Douglas (1997) and Wall (2001) with the methodological advancements of Guimarães et al. (2000Guimarães et al. ( , 2003 to model inter-municipal migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 56 publications
4
36
0
Order By: Relevance
“…In practice the index measures the hypothetical employment rate growth if the province grew at the national level over the time span under analysis. Changes in national industry are the exogenous shifters (Faggian et al, 2010). The third instrument is represented by the number of ATM machines per 10,000 inhabitants in 1996, which is exogenous with respect to migration flows in 2001, but highly correlated to the level of per-capita GDP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice the index measures the hypothetical employment rate growth if the province grew at the national level over the time span under analysis. Changes in national industry are the exogenous shifters (Faggian et al, 2010). The third instrument is represented by the number of ATM machines per 10,000 inhabitants in 1996, which is exogenous with respect to migration flows in 2001, but highly correlated to the level of per-capita GDP.…”
Section: Resultsmentioning
confidence: 99%
“…Although these approaches were seen as antagonistic at the beginning, and produced an intense debate (Schachter & Althaus, 1989;Evans, 1990Evans, , 1993Harrigan & McGregor, 1993;Graves & Mueser, 1993), it became clear over time that, in fact, they are not irreconcilable (see Faggian & Royuela, 2010). In migrating, people compare utility differentials across different alternative locations and these utility differentials are a function of both economic and non-economic (quality of life) factors.…”
Section: Introductionmentioning
confidence: 99%
“…The existing empirical evidence on Europe, despite the tendency of most studies to stress the prevailing importance of economic factors (see for instance Cheshire and Magrini 2006;Faggian and McCann 2009;Ritsilä and Ovaskainen 2001), has recently suggested that quality of life, tolerance and local 'creativity' also play an important role for urban (Faggian and Royuela 2010) and inter-regional (Biagi et al 2011) European migration. Non-economic factors play a key role also in explaining European migration flows: network effects and regional socio-environmental conditions exert a significant influence over the locational choice of migrants (Rodríguez-Pose and Ketterer 2012).…”
Section: Where To Go After Graduation? Jobs Creative and Tolerant Plmentioning
confidence: 99%
“…Although some articles consider count models using the number of migrants between origin and destination (Devillanova and García Fontés, 2004;Reher and Silvestre, 2009;Faggian and Royuela, 2010), most of the literature considers linear models in which the dependent variable is the migration rate or the log of migrants (recently, Clemente et al, 2016). Other works use micro data, analysing the propensity to migrate (Bover and Arellano, 2002;Reher and Silvestre, 2009).…”
Section: Recent Evidence On Migration Processes and The Case Of Spainmentioning
confidence: 99%
“…Given this utility function and following Faggian and Royuela (2010), k-th individual decides to move if the expected utility of a destination area j is higher than the expected reported utility of the origin area i plus the costs of moving, frequently proxied in the literature by the distance between i and j locations:…”
Section: Theoretical Approachmentioning
confidence: 99%